Wastewater Treatment in Italy: From Cost Centre to Strategic Investment - Francesco Perri (European Scientific Journal, ESJ, 2026)
Urban wastewater treatment has traditionally been framed as a regulatory obligation and a cost centre required to comply with environmental standards and mitigate the impact of discharges on aquatic ecosystems. However, in the context of increasing water scarcity, climate-related risks, and the broader ecological transition, this perspective is evolving. Wastewater is increasingly recognised not merely as waste to be disposed of, but as a potential strategic resource capable of generating environmental, economic, and social value. This study examines whether and to what extent wastewater treatment can be reframed as a strategic investment rather than a purely defensive environmental cost. The analysis adopts a structured qualitative policy-analysis approach, combining documentary analysis of European and Italian regulatory frameworks with quantitative evidence derived from institutional indicators and secondary data from international organisations. In addition, illustrative evidence on water reuse, energy recovery, and nutrient recovery is used to assess the contribution of wastewater treatment to circular economy processes. The research addresses three main questions: (RQ1) whether investments in wastewater treatment generate economic and social returns; (RQ2) how wastewater treatment contributes to circular economy dynamics through resource recovery; and (RQ3) what economic and environmental costs may arise from delayed or insufficient intervention, including regulatory sanctions, environmental damage, and the loss of recoverable resources. The findings suggest that investments in wastewater treatment can generate significant socio-economic benefits, particularly when treatment infrastructures enable water reuse, energy recovery, and resource valorisation. The analysis also highlights that delayed investment may produce substantial economic and environmental costs, reinforcing the relevance of the “cost of inaction” perspective. Finally, the study underscores the importance of integrated governance frameworks and long-term planning strategies, with particular attention to Southern Italy, where infrastructural gaps continue to generate environmental pressures and economic inefficiencies.